2013
DOI: 10.1111/cen.12041
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum adiponectin levels and age in healthy subjects and patients with type 2 diabetes

Abstract: Serum adiponectin levels are significantly and positively associated with age in healthy subjects and in patients with diabetes. This association is independent of renal function, body fat status, glucose metabolism and lipid profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 38 publications
8
52
3
Order By: Relevance
“…Our study also showed significant negative correlation with age and serum adiponectin levels. This finding was contradicted by Obata Y. et al, 10 2013 as they observed that serum adiponectin levels are significantly and positively associated with age in healthy subjects, but finding of our study was supported by Sunita J Ramanand et al, 11 2014 as they found that adiponectin levels decreases as age advances.…”
Section: Discussioncontrasting
confidence: 89%
“…Our study also showed significant negative correlation with age and serum adiponectin levels. This finding was contradicted by Obata Y. et al, 10 2013 as they observed that serum adiponectin levels are significantly and positively associated with age in healthy subjects, but finding of our study was supported by Sunita J Ramanand et al, 11 2014 as they found that adiponectin levels decreases as age advances.…”
Section: Discussioncontrasting
confidence: 89%
“…In healthy human individuals, plasma adiponectin levels increase with increasing age and an elevation of w1 mg/l of circulating adiponectin has been reported for every 10 years of age (Obata et al 2013). Moreover, plasma adiponectin levels are higher in women than in men (Obata et al 2013). Taking into account the wide range of variability of circulating adiponectin in healthy humans, strict cutoffs cannot be defined.…”
Section: Plasma Adiponectin Levelsmentioning
confidence: 99%
“…Taking into account the wide range of variability of circulating adiponectin in healthy humans, strict cutoffs cannot be defined. However, a crude estimation of plasma adiponectin levels in non-elderly healthy individuals is between 4 and 10 mg/l for males and between 6 and 15 mg/l for females (Isobe et al 2005, Obata et al 2013.…”
Section: Plasma Adiponectin Levelsmentioning
confidence: 99%
“…In the normal ovary, the granulosa cells express EGFR from the primordial follicle stage onward (Prigent et al 1992, Qu et al 2000, and during ovulation, LH surge stimulates mural granulosa cells to secrete EGF-like ligands, which subsequently bind to EGFR on cumulus cells surrounding the oocyte. This enables cumulus expansion, oocyte maturation, and ovulation (Park et al 2004).…”
Section: Discussionmentioning
confidence: 99%